2021
DOI: 10.1080/1040841x.2021.1907738
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus-related systemic diseases: clinical manifestation, evidence and pathogenesis

Abstract: Rotaviruses, double-stranded, non-enveloped RNA viruses, are a global health concern, associated with acute gastroenteritis and secretory-driven watery diarrhoea, especially in infants and young children. Conventionally, rotavirus is primarily viewed as a pathogen for intestinal enterocytes. This notion is challenged, however, by data from patients and animal models documenting extra-intestinal clinical manifestations and viral replication following rotavirus infection. In addition to acute gastroenteritis, ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 151 publications
(294 reference statements)
0
28
1
3
Order By: Relevance
“…As a double-stranded and non-enveloped ribonucleic acid virus, rotavirus is a major cause of life-threatening diarrhea in children worldwide, which was responsible for 29.3% of all diarrheal deaths among children under the age of 5 years in 2015 [2][3][4][5][6].…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…As a double-stranded and non-enveloped ribonucleic acid virus, rotavirus is a major cause of life-threatening diarrhea in children worldwide, which was responsible for 29.3% of all diarrheal deaths among children under the age of 5 years in 2015 [2][3][4][5][6].…”
Section: Dear Editormentioning
confidence: 99%
“…As a double-stranded and non-enveloped ribonucleic acid virus, rotavirus is a major cause of life-threatening diarrhea in children worldwide, which was responsible for 29.3% of all diarrheal deaths among children under the age of 5 years in 2015 [ 2 , 3 , 4 , 5 , 6 ]. Rotavirus enteritis greatly demonstrated pronounced seasonality and is typically considered a winter disease, especially in nonequatorial due to temperature and humidity changes that significantly affect rotavirus infection.…”
Section: Dear Editormentioning
confidence: 99%
“…Benign convulsions with mild gastroenteritis are among the most common neurological manifestations related to rotavirus infection in children, occurring in approximately 1%-8% of patients with rotavirus gastroenteritis. 14,[31][32][33][34] Although it has been documented worldwide, the number of reported cases is considerably higher in East Asian countries, particularly Japan, Korea, Taiwan, and China. [21][22][23][35][36][37] This clinical condition is seen in previously healthy children aged 1 month to 6 years (peaking in 1-2-year-olds) and present with afebrile (or febrile) seizures that develop 1-6 days after gastroenteritis onset.…”
Section: Clinicoradiological Features Of Rotavirus Infection-associat...mentioning
confidence: 99%
“…13) Rotavirus infection was initially considered confined to the gastrointestinal tract; however, many reports have shown that it may cause extra-intestinal manifestations including various neurological disorders, hepatitis, cholestasis, pancreatitis, type 1 diabetes, respiratory illness, myocarditis, renal failure, and thrombocytopenia. 14,15) Rotavirus is a common cause of acute encephalopathy and encephalitis in children. [16][17][18][19] Since the first report of central nervous system (CNS) involvement with rotavirus in 1978 (one fatal Reye's syndrome case, one encephalitis case), 20) a variety of rotavirus infection-associated CNS complications, such as convulsions with mild gastroenteritis, [21][22][23] aseptic meningitis, 24) mild encephalopathy with reversible splenial lesions, [25][26][27] encephalitis, 28,29) and cerebellitis, 30) have been documented.…”
Section: Introductionmentioning
confidence: 99%
“…Case reports and autopsy studies show further associations of AITD with viral infections: rubella virus in congenital illness ( 30 ), human T cell leukemia virus ( 31 ), Hantaan virus ( 32 ), hepatitis E virus ( 33 ), HIV ( 34 ) and – more recently – the Severe Acute Respiratory Syndrome Coronavirus-2 ( 35 39 ). In addition, various gastroenteric viruses have been detected in children with other autoimmune disorders such as celiac disease and type 1 diabetes ( 40 , 41 ).…”
Section: Introductionmentioning
confidence: 99%